Recent Advances in RP-HPLC Methods for Estimating Pharmaceutical Combinations: Focus on Tadalafil and Losartan Potassium - Jain, Khusboo; Sharma, Avneesh; Gulati, Puja (Journal of Neonatal Surgery, 2025)
Recent developments in the RP-HPLC methodology aimed at determining drug combinations with special emphasis on tadalafil and losartan potassium monitoring are the subject of this research study. Tadalafil and losartan potassium receive medical usage for managing benign prostatic hyperplasia (BPH) as well as hypertension and practitioners commonly prescribe them together to treat patients with multiple health conditions. The paper demonstrates how RP-HPLC functions as the optimal analytical tool because it delivers highly precise and reproducible drug separation and quantification methods for pharmaceutical compositions. This research work provides comprehensive information about method validation parameters alongside discussions of method development including accuracy and precision alongside linearity testing and application of RP-HPLC for pharmaceutical formulations analysis. The evaluation explains analytical limitations because the technique needs both selectivity and sensitivity in drug detection along with strategies for optimization. This study concludes that RP-HPLC demonstrates successful reliability as a routine analysis method but needs additional improvements to optimize its efficiency in pharmaceutical investigations.